In-situ tensile damage and fracture behavior of PIP SiC/SiC minicomposites at room temperature. Issue 14 (November 2021) - Yang, Haitang; Xu, Shenwei; Zhang, Daxu; Li, Longbiao; Huang, Xiaozhong
Abstract: In-situ tensile damage and fracture behavior of original SiC fiber bundles, processed and uncoated SiC fiber bundles, SiC fiber bundle with PyC interphase, SiC/SiC minicomposites without/with PyC interphase are analyzed. Relationships between load-displacement curves, stress-strain curves, and micro damage mechanisms are established. A micromechanical approach is developed to predict the stress-strain curves of SiC/SiC minicomposites for different damage stages. Experimental tensile stress-strain curves of two different SiC fiber reinforced SiC matrix without/with interphase are predicted. Evolution of composite's tangent modulus, interface debonding fraction, and broken fiber fraction with increasing applied stress is analyzed. For the BX™ and Cansas-3303™ SiC/SiC minicomposite with interphase, the composite's tangent modulus decreased with applied stress especially approaching tensile fracture; the interface debonding fraction increased with applied stress, and the composite's tensile fracture occurred with partial interface debonding; and the broken fiber fraction increased with applied stress, and most of fiber's failure occurred approaching final tensile fracture.